2013
DOI: 10.1002/ppap.201200104
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Plasma‐Activated Antimicrobial Solutions are Broad‐Spectrum and Retain their Efficacies for Extended Period of Time

Abstract: By applying dielectric-barrier discharge nonthermal plasma technique, we have treated fluids and generated antimicrobial solutions, tested for properties such as changes in pH, temperature, delay time, holding time, fluid-aging, and detection and comparison of acid and hydrogen peroxide. All plasma-treated solutions showed strong biocidal activity, and among them, NAC solution was the most powerful, inactivated biofilms of tested microorganisms in 15 min of holding time. During accelerated aging experiments, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
148
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(160 citation statements)
references
References 32 publications
11
148
0
1
Order By: Relevance
“…This is probably due to the increasing amount of plasma energy (J/cm 2 ) deposition in solution, and the associated chemical changes in solution that underlie. Our earlier observation demonstrated that response of biofilm eradication to plasma-activated fluid is exposure-time-dependent [9]. This trend was also observed during biofilm inhibition studies.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…This is probably due to the increasing amount of plasma energy (J/cm 2 ) deposition in solution, and the associated chemical changes in solution that underlie. Our earlier observation demonstrated that response of biofilm eradication to plasma-activated fluid is exposure-time-dependent [9]. This trend was also observed during biofilm inhibition studies.…”
Section: Resultssupporting
confidence: 61%
“…Surface disinfectants have a major role in eradication of biofilms in this regard. Plasma can either be applied directly to biofilm bearing surface [8] or biofilm can be treated with plasma-treated fluids to inactivate embedded pathogens [9]. Biofilm curing or treatment has been demonstrated using different plasma systems by many investigators [16]- [21], but not the system, set up, and approach we used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10) PAL has a good shelf-life with a reported retention of its antibacterial activity from days to weeks 7,15) to even years. 16) Apart from water, plasma-treated aqueous buffer and cell culture media are being investigated for cancer therapy. [17][18][19][20] It is without question that the bacteriostatic activity of PAW and other aqueous plasma-treated solutions is predominantly governed by reactive oxygen and nitrogen species (RONS).…”
Section: Introductionmentioning
confidence: 99%